The Genre of Biography and Changes in Understanding Historicity - Sixta, Václav (Dějiny – teorie – kritika, 2018)
This contribution investigates the relation between biography as a genre and changes in the understanding of historicity which took place in Late Modernism. The author introduces various theoretical inspirations based on the texts of Gilles Deleuze and Françoise Hartog, which could help us grasp the shift in approaching the category of time in Late Modernism. These inspirations are then applied to various forms of biography in current culture of remembrance. Materials the author analyses include for instance biographic series of various publishers, a collection of biographies of Václav Havel, campaign of the Kefírer brand, or project Opráski Sčeskí Historje. These materials are studied from the perspective of their relation to the past which they can help create. The author asks whether these sources deal with national history oriented towards future or with nostalgic recollections devoid of substantive social content. In conclusion, the author proposes a typology of relations to the past as mediated by biographies and offers an explanation of success of this genre within the current culture of remembrance.